Fermentative Lactic Acid Production From Lignocellulosic Feedstocks: From Source to Purified Product - Yankov, Dragomir (Frontiers in Chemistry, 2022)
The second (lignocellulosic biomass and industrial wastes) and third (algal biomass) generation feedstocks gained substantial interest as a source of various value-added chemicals, produced by fermentation. Lactic acid is a valuable platform chemical with both traditional and newer applications in many industries. The successful fractionation, separation, and hydrolysis of lignocellulosic biomass result in sugars’ rich raw material for lactic acid fermentation. This review paper aims to summarise the investigations and progress in the last five years in lactic acid production from inexpensive and renewable resources. Different aspects are discussed – the type of raw materials, pretreatment and detoxification methods, lactic acid-producers (bacteria, fungi, and yeats), use of genetically manipulated microorganisms, separation techniques, different approaches of process organization, as well as main challenges, and possible solutions for process optimization.